Differentiated service and ant colony optimization based routing protocol for wireless multimedia sensor networks - Yan-jing SUN; Wei FANG; Wei-dong LIU; Chong MENG (Tongxin xuebao)
There are many kinds of data in wireless multimedia sensor networks,which have different quality of service requirements.A novel routing protocol(DSACO)based on ant colony optimization was proposed.In the protocol,the time and energy spent on searching paths were reduced by limiting ants searching region after dividing the network into many layers.The protocol chose different paths for different kinds of data to meet the QoS requirements from the data.The simulation results show that the protocol provides better QoS for multimedia data and outperforms the other routing protocol in terms of data transmission average delay,packet loss rate and energy consumption.